Dual chromic-dichroic modulation in plasmonic metasurfaces for enantioselective electrochromism - Kim, Ju Hwan; Han, Jang-Hwan; Kim, Gyurin; Kim, Doeun; Song, Young Min; Jeong, Hyeon-Ho (ACS nano, 2025)
Plasmonic electrochromic devices promise a vibrant, high-resolution color control for outdoor displays and optical memory, but achieving broadband tunability within a single nanopixel remains a challenge. Here, we present a chiral plasmonic metasurface composed of wafer-scale arrays of gold nanohelices conformally coated with polyaniline (PANI). The nanohelices give rise to strong circular dichroism, while the PANI shell enables the electrochromic modulation of plasmonic resonances, together realizing dual chromic-dichroic modulation. This plasmonic metasurface thus achieves polarization- and voltage-dependent color dynamics spanning a 287 nm spectral range with a sub-1 V operation. It operates at low power (1.3 mW/cm2), retains color states for over 15 min, and exhibits enantioselective electrochromism, where mirror-symmetric chiroptical dynamics enable multidimensional optical logic. A four-pixel prototype demonstrates 162 distinct optical states, establishing this scalable, energy-efficient metasurface as a promising platform for outdoor displays, encrypted optical memory, and reconfigurable photonic computing.